PENGARUH AKURASI INFORMASI ICE CREAM MIXUE DI INSTAGRAM TERHADAP INTEGRITAS PADA FOLLOWERS - Dewi, Azkia Cintana; Agustini,; Ruhimat, (Karimah Tauhid, 2023)
Social media is a means for every individual to express themselves by conveying aspirations in the form of information and can also be a means of disseminating information. The quality of information on an Instagram account must of course be accurate and clear so that followers can understand the information. This study aims to determine the effect of the accuracy of Mixue ice cream information on Instagram on the integrity of Mixue to followers. The research method uses descriptive quantitative. Primary data collection techniques using questionnaires and secondary data with online journals, articles, and books. The research data analysis technique uses WMS (Weighted Mean Score), and simple linear regression statistical tests. Likert scale result measurement. The results of the study prove that the accuracy of Mixue ice cream information on Instagram has a positive and significant effect on Mixue's integrity to followers in increasing followers' trust. The conclusion is that if Mixue ice cream information on Instagram is made accurately, Mixue's honesty and loyalty will be further enhanced to followers.